Diazirine-containing tag-free RNA probes for efficient RISC-loading and photoaffinity labeling of microRNA targets. Issue 17 (15th September 2018) - Nakamoto, Kosuke; Akao, Yukihiro; Ueno, Yoshihito
Graphical abstract: Highlights: Synthesis of a photo-reactive and tag-free RNA probe for the identification of microRNA (miRNA) targets is described. The RNA probe can crosslink with a complementary RNA by UV irradiation. The crosslinked RNA probe can be rapidly tagged by Cu-catalyzed azide alkyne cycloaddition (CuAAC). The photo-reactive and tag-free miRNA-145 probe shows comparable gene silencing activity to that of unmodified miRNA-145. Abstract: We designed and synthesized a photo-reactive and tag-free RNA probe for the identification of microRNA (miRNA) targets. To synthesize the RNA probe, we designed a novel nucleoside analog 1- O -[3-ethynyl-5-(3-trifluoromethyl- 3H -diazirine-3-yl)]benzyl-β-d -ribofuranose containing aryl trifluoromethyl diazirine and ethynyl moieties. The RNA probe containing this analog was observed to form crosslinks with complementary RNA by UV irradiation and was rapidly tagged by Cu-catalyzed azide alkyne cycloaddition (CuAAC). In addition, the tag-free and photo-reactive miRNA-145 probe showed comparable gene silencing activity to that of unmodified miRNA-145. Therefore, miRNA probes containing the nucleoside analog are promising candidates for the identification of target mRNAs of miRNAs.